2015
DOI: 10.3389/fnbeh.2015.00185
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor organization of a sustained involuntary movement

Abstract: Involuntary movements share much of the motor control circuitry used for voluntary movement, yet the two can be easily distinguished. The Kohnstamm phenomenon (where a sustained, hard push produces subsequent involuntary arm raising) is a useful experimental model for exploring differences between voluntary and involuntary movement. Both central and peripheral accounts have been proposed, but little is known regarding how the putative Kohnstamm generator responds to afferent input. We addressed this by obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 62 publications
5
33
0
Order By: Relevance
“…We found that during bilateral Kohnstamm, inhibition of one arm did not affect the EMG signal in the other arm. This suggests that there are separate Kohnstamm generators for each arm, potentially located in each contralateral hemisphere, and is consistent with earlier reports (De Havas et al, 2015; but see for evidence of interlimb coupling).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that during bilateral Kohnstamm, inhibition of one arm did not affect the EMG signal in the other arm. This suggests that there are separate Kohnstamm generators for each arm, potentially located in each contralateral hemisphere, and is consistent with earlier reports (De Havas et al, 2015; but see for evidence of interlimb coupling).…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence for central (Duclos, Roll, Kavounoudias, & Roll, 2007;Solopova, Selionov, Zhvansky, Gurfinkel, & Ivanenko, 2016) and peripheral (Hagbarth & Nordin, 1998) contributions to the Kohnstamm phenomenon. Afferent input from the periphery can temporarily 'gate' motor output to the muscle (De Havas et al, 2015), while large changes in visual input have been shown to switch motor output from the muscle active during the induction to its antagonist (Ghafouri, Thullier, Gurfinkel, & Lestienne, 1998;Gilhodes, Gurfinkel, & Roll, 1992). Control processes for the Kohnstamm phenomenon may involve multiple regions of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed by a recent investigation (Fig. 3b), which found that obstructing the aftercontraction caused the increasing linear trend in agonist EMG to reach a plateau level (De Havas et al 2015). Thus, afferent signalling from the agonist muscle can affect the aftercontraction.…”
Section: Research Themessupporting
confidence: 83%
“…Complex interactions occur between muscle groups (Bellincioni 1926; Craske and Craske 1985), while sensory input can interact with the aftercontraction in surprising and divergent ways (Brun et al 2015; Brun and Guerraz 2015; De Havas et al 2015; Forbes et al 1926; Ghafouri et al 1998). As such, it may be necessary to consider hybrid models, combining both central and peripheral mechanisms, to explain the Kohnstamm phenomenon.…”
Section: Research Themesmentioning
confidence: 99%